Creative economy in the urban agglomeration of Seville: stakeholders, local cooperation networks and main actions - Inmaculada Caravaca Barroso, Gema González Romero; Víctor Fernández Salinas, Antonio García García (Boletín de la Asociación de Geógrafos Españoles, 2013)
Resumen